Axe-heads and identity : an investigation into the roles of imported axe-heads in identity formation in Neolithic Britain - Walker, Katharine (Archaeopress Publishing Ltd, 2018)
This volume seeks to re-assess the significance accorded to the body of stone and flint axe-heads imported into Britain from the Continent which have until now often been poorly understood, overlooked and undervalued in Neolithic studies.